(3GdhLjRs - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfi eJMac CjgG GdSGFd GdedWa HgPG GdhLjR GdPi GTJOJ Edjg VQhQJc s
(3BNQgG (B:s
(3hEf cGfG eYSQjf afUa GdhdG dcd hGMO efgeG hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3hQO CjVkG JMJ Qbe (B" 156" (3abg TGaYi (B" (3NGOe GdQhVI hGdQGaYi (B" s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B2002s
Keywords: (3Gdabg GdTGaYjs